State of the industry for drug–diagnostic development: challenge and change on the path to precision medicine. (July 2016) - Milne, Christopher-Paul; Cohen, Joshua; Chakravarthy, Ranjana; Awatin, Josephine
Four challenges to the adoption of personalized medicine were identified in the mid-2000s – adherence to the blockbuster model, the lack of a supportive regulatory environment, the dysfunctional payment system and physician barriers. In this article, we report on our study findings based on interviews with 24 senior executives from leading drug and diagnostics companies to assess progress made in addressing those challenges over the last decade. Overall, we found that even with payer pushback and adjusting to new business models, the majority of developers expected their business to increase over the next 5 years. Several factors that unexpectedly helped to shape the personalized medicine landscape, such as the growth of support in genomic medicine from the public sector, are also discussed.